The Little Data Book on Private Sector Development 2014 - World Bank (Washington, DC, 2014)
Reliable cross-country data on aspects of private sector development are crucial in planning for economic recovery and growth. In targeting increased exports and investment, many governments prioritize an improved climate for business as a basis to attract capital, create jobs, and provide basic services. The availability of cross-country data on the business environment has rapidly expanded in recent years, including data from the World Bank Group s Doing Business project, Enterprise Surveys, and the Entrepreneurship Snapshots. Included in this guide are indicators on the economic and social context, the investment climate, private sector investment, finance and banking, and infrastructure. Though a pocket guide cannot include all relevant variables, the included indicators provide users with a general understanding of the private sector in each country. Indicators displayed in the tables are defined in the glossary, which also lists data sources.